INFLUENCE OF HEALTH SERVICE ACCEPTANCE VALUE TOWARD A PATIENT RELIANCE - Sri Sustariyah (JEES: Journal of Economic Empowerment Strategy, 2018)
The Government appointed Social Health Insurance Administering Body or BPJS Kesehatan. Alleged implementation of operational implementation of Social Security Health is still not yet fully understood and perceived benefits and services by the community, Marketing with a system of proximity to customers and provision of quality services to be one strategy that is effective in improving public confidence. Relational marketing and service quality is a determinant factor in increasing value and trust for customers. The purpose of this study is to analyze the influence of relational marketing and service quality to customer value and its impact on customer trust. The method used is quantitative with expert judgment. The sample of this research is inpatient of BPJS health participant at Public Hospital owned by Local Government in West Java Province. Technique of data retrieval is done by cluster proportional random sampling and analysis technique used is SEM analysis (structural equation modeling). The results of descriptive research indicate that relational marketing, service quality, customer value and customer trust move from less good to sanga tbaik. The results of the study of each indicator is still found some less than optimal. The result of verifikatif research proves that relational marketing and service quality have positive and significant effect to customer value and customer value have positive and significant influence to customer trust.